Good Corporate Governance in Mediating the Effects of Intellectual Capital and CSR on Company Performance: Empirical on BUMN in Indonesia - Salviantono, Brian; Paminto, Ardi; Ulfah, Yana (International Journal of Finance Research, 2022)
Finance is a vital aspect for companies, especially State-Owned Enterprise (BUMN). In Indonesia, the trend of financial markets determines the company’s profit. It oriented this study to get empirical evidence about the effect between intellectual capital and corporate social responsibility (CSR) on company performance, where the relationship is determined by good corporate governance (GCG) which acts as a moderator for BUMN companies. The sample includes 13 state-owned companies listed on the Indonesia Stock Exchange (IDX) through a purposive sampling stage. Interpreting the data using the model is the SEM structural equation method (SEM) for the period 2012-2020. The statistical software is supported by SmartPLS. The results of the analysis conclude that intellectual capital and CSR have a significant effect on company performance. Then, GCG has no significant effect on the relationship between intellectual capital and company performance. Interestingly, GCG also does not significantly moderate the relationship between CSR and company performance. The limitations of the study need to be discussed.